Assessing the OA impact effect for hybrid journals - Oefelein, Timon (Septentrio Conference Series, 2018)
This poster showcases the key findings from two multidisciplinary studies that explore the impact advantage of OA in hybrid journals. The studies were recently carried out by Springer Nature in collaboration with Digital Science and are available in the form of a White Paper. The first study takes a global look and compares the impact - as measured by citations, downloads, and altmetric data - of 70 921 non-OA articles to 3004 OA articles. Both article sets were published in the same time frame and journal portfolio. The second study takes a country focus on articles published by corresponding authors affiliated with the United Kingdom: over 3087 OA articles are compared to 6027 non-OA articles. The global studies contain controls for: journal impact factor, subject field, institutional ranking, and geography. Key results include descriptive statistical data as well as predictive models. Both studies are based on Springer Nature’s hybrid journal portfolio, which allows researchers globally to continue to publish in the same journals as each other regardless of their funder or country’s position on open access, supporting the cohesion of scientific communities and author choice.